Perancangan Sistem Informasi Pendaftaran Security Pada PT. Reksa Buana Nata Berbasis Web Menggunakan Metode Waterfall - Nurul Syifa Fauzia Paksi; Dewy Suciati; Melisa Dwi Hestiani; Thoyibbah T. (CV. Multi Kreasi Media, 2023)
Reksa Buana Nata is a Security Services Business Entity (BUJP) or institution that provides education and training for Gada Pratama or security guards who can produce prospective security personnel who are professionals in the field of security. How to register with BUJP can be done by visiting the BUJP office directly. Using manual methods like this is feared that there can be missing forms and participant requirements as well as queues on registration. To minimize this, it is necessary to have a better registration media by designing a website-based online application for PT. Reksa Buana Nata Mutual Fund. The application was tested using the waterfall method. Testing using the waterfall method can minimize errors because it has a clear and more detailed flow.